1987
DOI: 10.1152/ajprenal.1987.252.1.f65
|View full text |Cite
|
Sign up to set email alerts
|

Control of renal hemodynamics in hyperglycemia: possible role of tubuloglomerular feedback

Abstract: The purpose of this study was to test the hypothesis that hyperglycemia, comparable with that found in uncontrolled diabetes mellitus, increases renal blood flow (RBF) and glomerular filtration rate (GFR) through a tubuloglomerular feedback (TGF) mechanism. We infused glucose intrarenally (0.1-0.3 g/min) into anesthetized dogs with normal kidneys (NK), with nonfiltering kidneys (NFK) in which changes in TGF were blocked, and with normal kidneys in which renal perfusion pressure (RAP) was lowered to the limits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
52
2
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 0 publications
7
52
2
1
Order By: Relevance
“…The maximal decrease in bp was seen with combination treatment. The increase in systolic bp in diabetes mellitus could be related to the stimulatory effect of hyperglycaemia on the RAS [36,37,38] or generation of oxygen radical species reducing the availability of nitric oxide [39]. A normalisation of systemic bp in nonselective ET-1 blockade in diabetic rats is described [40].…”
Section: Discussionmentioning
confidence: 99%
“…The maximal decrease in bp was seen with combination treatment. The increase in systolic bp in diabetes mellitus could be related to the stimulatory effect of hyperglycaemia on the RAS [36,37,38] or generation of oxygen radical species reducing the availability of nitric oxide [39]. A normalisation of systemic bp in nonselective ET-1 blockade in diabetic rats is described [40].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is highly likely that other mechanisms are operative to at least some extent. For example, acute intrarenal hyperglycemia has been shown to increase renin secretion due to stimulation of proximal tubular sodium reabsorption (46). Thus the sympathetic nervous system was required for the progressive increase in PRA, and that action seemed to account for most of the blood pressure effect of adrenergic blockade.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that tubuloglomerular feedback may be altered by hyperglycemia (23)(24)(25). The (26).…”
Section: Discussionmentioning
confidence: 99%